Kinetics of hydrate formation, dissociation and reformation - Bjørn Kvamme (Chemical Thermodynamics and Thermal Analysis, 2021)
Hydrates in natural sediments are never able to reach thermodynamic equilibrium because of in balance between number of independent thermodynamic variables and constraints (conservation and equilibrium conditions). In this work I present a consistent thermodynamic approach in which all components in all phases have the same reference state (ideal gas). Gibbs free energy and Enthalpy are modelled within the same concept and thermodynamic consistency is demonstrated though couplings between classical thermodynamics and statistical mechanics. The use of residual thermodynamics for all phases provides unique tools for comparing stability of different phases in terms of free energy. This is particularly important for hydrates forming from different phases. Since thermodynamic equilibrium is not possible then chemical potentials for guest molecules are not the same in each phase, Heterogeneous hydrate formation on gas/liquid interface will result in different hydrate than hydrate forming from dissolved hydrate former in water. It is also demonstrated that hydrate stability cannot be discussed in terms of independent thermodynamics variables like for instance temperature and pressure. As specific example we show that carbon dioxide is more stable than methane hydrate over the whole range of temperature and pressure. I also demonstrate that it is possible to modify Classical Nucleation Theory (CNT) though inclusion of a new mass transport term that also introduces an interface to the theory. As illustration we show that the modified CNT is able to predict experimental induction times for methane hydrate and carbon dioxide with very reasonable values for diffusivity coefficients on the liquid water side of hydrate/liquid water interface.